Developmental Toxicity and Thyroid Endocrine Disruption of Polyhexamethylene Guanidine Hydrochloride and Humidifier Disinfectant in Zebrafish Larvae - Suhyun Park; Hyojin Kim; Kyunghee Ji (Applied Sciences, 2021)
Polyhexamethylene guanidine (PHMG), a major component of humidifier disinfectants (HDs), is responsible for the outbreak of pulmonary diseases in pregnant women and children in South Korea. This study aims to characterize the developmental toxicity and thyroid endocrine disruption of Vegetable Home Cleanup HD and its main component, PHMG-hydrochloride (PHMG-H), in zebrafish embryo/larvae after a 7-d exposure. Acute lethality, development, whole-body thyroid hormones, and transcription of genes related to the hypothalamus-pituitary-thyroid axis were investigated. Zebrafish embryos exposed to the actual-use concentration (0.6%) of HD exhibited significant embryo coagulation and larval mortality. The concentration of triiodothyronine (T3) was significantly high in fish exposed to 0.4 mg/L PHMG-H, accompanied by the downregulation of the tshβ gene. These results suggest a feedback mechanism for the regulation of increased T3 levels. Significant decrease of thyroxine (T4) concentration, increase of T3/T4 ratio, and upregulation of the deio2 gene in fish exposed to PHMG-H suggested that there was an increase in the active T3 due to the catalysis of outer ring deiodination. Future research is required to determine the factors that contribute to the differences in toxicity between the two counter ions of PHMG.